1996
DOI: 10.2508/chikusan.67.511
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships Among Traits Recorded at Registry Judgment, Reproductive Traits of Breeding Females and Carcass Traits of Fattening Animals in Japanese Black Cattle

Abstract: Genetic relationships among traits recorded on breeding females and carcass traits of fattening animals in Japanese Black cattle were estimated using REML procedure under multiple-trait animal models. Traits analyzed were five exterior judging traits, three body measurements at registry judgment, two reproductive traits (age at first calving, AFC; average calving interval, ACI) of breeding females and five carcass traits collected in Hiroshima prefecture. Heritabilities of exterior judging traits, body measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 13 publications
5
19
1
1
Order By: Relevance
“…The heritability estimation for AFC in this study correspond well with Oyama et al (2004) who reported that heritability estimation of AFC for Japanese black cattle was 0.20. However, this value was higher than those usually found in literature for tropical cattle.…”
Section: Age At First Calvingsupporting
confidence: 90%
See 2 more Smart Citations
“…The heritability estimation for AFC in this study correspond well with Oyama et al (2004) who reported that heritability estimation of AFC for Japanese black cattle was 0.20. However, this value was higher than those usually found in literature for tropical cattle.…”
Section: Age At First Calvingsupporting
confidence: 90%
“…Heritability estimations for reproductive traits of different beef cattle breeds have been reported by several studies (Oyama et al, 2004Borman et al, 2006Goyace and Guiterez, 2001). Oyama et al (2004) estimated heritability of reproductive performance in Japanese black cattle including age AFC, CI and days opens (DO) were 0.20; 0.05 and 0.05 respectively.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Using multivariate models, heritability values higher than those of this study in the first (0.16) and second (0.19) parity have been found, as well as between the third and ninth (0.17) parity and a heritability of 0.09 for the DO in subsequent parities (Goyache et al, 2005). Estimates of lower values (0.05) were published for the Japanese Black cattle (Oyama et al, 2004). An important component of DO is the length of postpartum anestrus, which has registered a moderate heritability (0.38) in Charolais cattle when the estimate was based on the days between calving and the first increase in blood progesterone; however, heritability index was reduced to 0.11 when it was estimated based on the first estrus observed (Mialon et al, 2001).…”
Section: Discussioncontrasting
confidence: 44%
“…A 12‐month calving interval, i.e. one calf per year, has been a management target in Japanese cow–calf production from an economic viewpoint, as described in Oyama et al . (1996).…”
Section: Resultsmentioning
confidence: 99%